PENGARUH PEMBERIAN PUPUK BOKASHI TERHADAP PERTUMBUHAN VEGETATIF RUMPUT GAJAH (Pennisetum purpureum) - Kastalani Kastalani (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
The aim of this research were to know the effect of bokashi that giving the best result to growth vegetative Elephant grass (Pennisetum purpureum). This research wad design by using Completely Random Design (CRD) with single factor experiment that is doses bokahsi (B), with thelevel of each doses, b0= control (without bokashi), b1= 10 ton ha-1, b2= 20 ton ha-1, b3= 30 ton ha-1. The result showed that the applications bokashi giving the influence to of Elephant grass (Pennisetum purpureum) Bokashi 30 ton ha-1 give the highest production Elephant grass (Pennisetum purpureum).